Effects of rifle carriage on skiing biomechanics in biathlon - Linnamo, V.; Ohtonen, O.; Mikkola, J.; Rauhamäki, H.; Lindell, P.-O.; Lindinger, S. J.; Kuitunen, S. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Carrying a rifle may account for about 7 % of the total energy expended on skiing on a flat terrain (Frederick 1987) and increase 8 % of the oxygen uptake when skiing on a treadmill (Rundell & Szmedra 1998). However, Millet et al. (1998) did not find any changes in metabolic cost, joint kinematics, EMG or cycle rate in roller ski skating on a track using a weighted west. It appears that the effects of rifle carriage on skiing biomechanics are not yet well understood, especially in natural snow conditions. The aim of this study was to examine the effects of rifle carriage on skiing biomechanics.